A constituição do sentimento religioso: da experiência do desamparo primordial à elaboração de um ideal vocacional - Ruprecht, Rubens [UNESP] (Universidade Estadual Paulista (Unesp), 2004)
No alvorecer da psicanálise, Freud estabelece a noção da natureza humana como fendida, clivada, fundando uma nova noção de realidade psíquica, na qual a descoberta da verdade está relacionada à verdade do desejo inconsciente, e a religião seria uma ilusão desejante, a transformação de um passado idealizado num futuro cambiante, prenhe de um desejo em constante metamorfose. No patamar da religião, essa supervalorização do ideal, diante da desvalorização do real, remete o sujeito a um estado de infantilização pelo pensamento mágico-infantil. Na presente pesquisa, foram analisados quatro sujeitos, estudantes de teologia protestante, em cujas entrevistas foram analisados alguns aspectos relacionados ao desamparo e à idealização religiosa, integrantes basilares da sua dinâmica vocacional /profissional, no contexto de um Seminário Teológico protestante. As análises nos permitem afirmar que o sentimento religioso se mantém por seus vínculos com as figuras paternas idealizadas, que confirmam a fantasia infantil de plenitude que diminuem o sofrimento imediato, mas infantilizam o sujeito, ao invés de buscarem sua superação, como proposto pela psicanálise. Supõe-se que a superação dessa condição humana não implica necessariamente na remissão total do sofrimento psíquico, mas na capacidade do sujeito em adquirir uma suportabilidade capaz de tolerar a falha...

At the dawn of psychoanalysis, Freud determines the notion of human nature as split, creating a new notion of psychic reality in which the truth discovery is related to the truth of unconscious desire and the religion would be a desirable illusion, the change of an idealized past into a convertible future, full of desire in constant metamorphosis. According to religion, this overestimate of ideal, beside the depreciation of reality, refers the person to a state of infantilism through the magic-infantile thought. Four students of Protestant Theology were analyzed in this study. The data were collected through interviews and some aspects related to both helplessness and religious idealization, which ones can be considered basilar integrants of their vocational/professional dynamics, in the context of a Protestant Theological Seminary were analyzed. The results showed that the religious feelings are supported by their ties with the idealized paternal figures that confirm the child fantasy of completeness through which the immediate suffering is decreased, but they make the person a child rather than seeking their overcoming as proposed by psychoanalysis. It is assumed that the overcoming of this human condition does not mean the person is protected against the total psychic suffering, but it results in person's capacity of supporting, being able of tolerating the fault, failure and helplessness without them representing a very hard threat to their psychic structure. Therefore, the constitution of religious feelings follows both given intra-psychic and external social determinism that... (Complete abstract, click electronic access below)
Keywords: Psicanalise; Alienação (Psicologia social); Psicopatologia; Psychoanalysis; Psychic reality; Ilusion; Helplessness; Idealization